Combination of lean thinking and A3 problem-solving methods to reduce the cost of purchasing cleaning agents in a paint manufacturer in Indonesia - Hibarkah Kurnia; Krisna Budi Juliantoro; Suhendra Suhendra; Ahmad Turmudi Zy; Apriyani Apriyani (Universitas Mercu Buana, 2024)
One of the manufacturing industries for making solvent-based and water-based paints is located in the Cikarang area, West Java. This paint company is experiencing an increase in production due to a large number of requests for various products. The company's level of cleanliness in maintaining quality and reducing waste of operational costs is the key to the company's success in becoming an international standard company. Every year the company incurs the cost of purchasing a cleaning agent imported from Norway because it is a basic requirement in material inventory to meet customer satisfaction. The purpose of this research is to reduce the wasted costs of purchasing cleaning agents originating from imports, maintaining 5S conditions, and fulfilling customer satisfaction. The method used in this study is a combination of the lean thinking method and the most effective A3 problem-solving method which can help create consistent, clear, and structured problem-solving documentation. This research found that there is a very large cost to buy a cleaning agent in 2021 of IDR 114,331,430 which must be spent by companies in using cleaning agents. The results of this study found that there was a reduction in the cost of purchasing a cleaning agent in 2022 to IDR 4,897,900. Therefore this paint company gets operational cost savings in purchasing cleaning agent materials of 97.71%.